PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPEMUDAAN DAN OLAHRAGA KOTA TANGERANG SELATAN - Loveita Lutsy; Retno Japanis Permatasari (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of work motivation and job satisfaction on employee performance at the Pamulang District Office, South Tangerang City. The method used is quantitative associative. The research population was 53 people and using a saturated sample or the entire existing population as a sample in this study. The data analysis technique used is instrument test, classical assumption test, descriptive analysis, regression test, correlation coefficient test, coefficient of determination test and hypothesis test. The research results show that work discipline partially affects employee performance by 50,5%  while the remaining 49,5% is influenced by other variables not examined. Motivation partially affects employee performance by 37,2% while the remaining  62,8% is influenced by other variables not examined. Work discipline and Motivation simultaneously affect employee performance by 42,8% while the remaining 47,2% are influenced by other variables not examined. The results showed that the multiple linear regression equation Y = 12,592 + 0,468 X1 + 0,212 X2 means that employee performance even without the influence of work motivation and job satisfaction already has an effect of 12,592. Simultaneously, work discipline and motivation have a positive and significant effect on employee performance. This is evidenced by the value of F count > F table, namely (27,971 > 3,18) with a significance of 0.001 <0.05, so H0 is rejected and H3 is accepted, meaning that there is a positive and significant influence between work motivation and job satisfaction on employee performance simultaneously at the Youth and Sports Department Office of South Tangerang City